Regesten zur Geschichte der Juden in Österreich, Band 3: 1366-1386 Band 3: 1366-1386 - Brugger, Eveline (Studien Verlag, 2015)
The remarkably high number of medieval sources on the history of Austrian Jews allows for insights into the economic, legal, and social standing of the Jews as well as into how the Christian environment treated them. The sources published in this volume show the decline in the economic and legal position of the Jews; while they were largely safe from open persecution, they were subjected to more and more restrictions that aimed at mere financial exploitation. In addition to that, the sources provide insights into the everyday interaction of Jews with the Christian majority.